Network Coding Schemes and Cooperative Communication Systems Amplify and Forward in Outdoor Environments - Khair, Ummul; Dahlan, Andi Ahmad; R, Ihsan Lumasa; Nita, Sri; Veronica, Vera (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Fading is a phenomenon of decreasing signal strength during transmission, caused by changes in environmental conditions or physical obstacles in the propagation path. Fading can cause interference in signal reception, such as distortion or loss of information, especially in Non-Line of Sight (NLoS) paths, where signals must pass through many paths or obstacles such as buildings, trees, or other objects. To eliminate fading interference, a cooperative communication system is created to reduce the effects of fading in wireless networks. The cooperative communication system works by utilizing other nodes in sending signals to the destination. The relay protocol used in this study is amplify and forward, where the signal to be sent will be amplified and forwarded to the destination by the relay node. A network coding scheme is added to the cooperative communication system to improve network performance. This scheme encodes each piece of information with the XOR technique. The parameters used in measuring the network coding scheme in the cooperative communication system are BER and throughput. Viewed from the BER value, the conventional cooperative communication system has better performance compared to the cooperative communication system with network coding. Cooperative communication system scheme without NC BER value is 0 when the transmit power value is -19 dBm or Gain 32. While for the cooperative communication system scheme with network coding BER value is 0 when transmit power of -9.25 dBm. Throughput system with network coding has increased by 17% compared to the conventional system.